Ultrasound-assisted ionic liquid-mediated green method for synthesis of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidines, their anti-tubercular activity, molecular docking study and ADME predictions - Baddepuri, Sravanthi; Gamidi, Rama Krishna; Kumari, Jyothi; Sriram, Dharmarajan; Basavoju, Srinivas (New Journal of Chemistry, 2024)
The aim of the study is to develop the synthesis of a novel series of potent anti-tubercular (anti-TB) activity of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidine derivatives via an efficient green approach achieved by using an ionic liquid ([Bmim]BF4) under ultrasonication. The title compounds 4a-4ad with a general molecular formula CaHbX(0-2)NcOd (X = F/Cl/Br) were produced with high yields in shorter reaction time and well characterized by using spectral techniques; and finally single crystal X-ray diffraction method (4b). The newly synthesized compounds were evaluated for their in vitro anti-TB activity against Mycobacterium tuberculosis H37Rv strain. Among all, six compounds 4e (C36H29N5O4), 4g (C34H28N4O3), 4q (C36H28F2N4O2), 4r (C36H28ClFN4O2), 4y (C36H29BrN4O2) and 4z (C36H28BrFN4O2) exhibited significant anti-TB activity with MIC value 6.25 mu g mL-1, when compared to the standard drug ethambutol (MIC:1.56 mu g mL-1). In silico molecular docking studies were performed against M. tuberculosis enoyl-acyl carrier protein reductase inhibitor. The compounds 4o, 4p, 4y and 4aa were exhibited least binding energies -12.58, -12.61, -12.58 and -12.57 kcal mol-1, respectively. These results reveal that the produced compounds might be used for the future generation of novel anti-TB drugs. The study aims to develop and synthesis of a novel series of 1,3-diphenylpyrazole-based spirooxindolopyrrolizidine derivatives as potent anti-TB agents via an efficient green approach by using an ionic liquid ([Bmim]BF4) under ultrasonication.